2015
DOI: 10.1007/s12630-015-0327-x
|View full text |Cite|
|
Sign up to set email alerts
|

Imagerie préopératoire par résonance magnétique du cerveau et délirium postopératoire après pontage coronarien à cœur battant: une étude prospective de cohorte

Abstract: Background Delirium after cardiac surgery is a serious complication, increasing morbidity and mortality. Despite its high expectations, off-pump coronary artery bypass grafting (OPCAB) has largely failed to reduce the incidence of postoperative neurological complications. To further investigate the reasons for this failure, we used perioperative brain magnetic resonance imaging (MRI) to determine the relation between MRI findings and postoperative delirium. Methods Altogether, 98 patients undergoing elective O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Subclinical cerebral ischemic lesions detected on diffusion‐weighted magnetic resonance imaging (DWI lesions) appear to affect more than 70% of individuals undergoing TAVR . Analogous to observations in cardiac surgery, these lesions may play an important role in the pathophysiology of delirium after TAVR . Whether cerebral embolic protection devices reduce the incidence of IHPOD remains unclear because of the multifactorial nature of this cognitive disorder, although a recent study investigating the use of a filter‐based cerebral embolic protection device during TAVR found less IHPOD in individuals in the filter group (3%) than in those without a filter (15%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subclinical cerebral ischemic lesions detected on diffusion‐weighted magnetic resonance imaging (DWI lesions) appear to affect more than 70% of individuals undergoing TAVR . Analogous to observations in cardiac surgery, these lesions may play an important role in the pathophysiology of delirium after TAVR . Whether cerebral embolic protection devices reduce the incidence of IHPOD remains unclear because of the multifactorial nature of this cognitive disorder, although a recent study investigating the use of a filter‐based cerebral embolic protection device during TAVR found less IHPOD in individuals in the filter group (3%) than in those without a filter (15%) .…”
Section: Discussionmentioning
confidence: 99%
“…49 Analogous to observations in cardiac surgery, these lesions may play an important role in the pathophysiology of delirium after TAVR. 50,51 Whether cerebral embolic protection devices reduce the incidence of IHPOD remains unclear because of the multifactorial nature of this cognitive disorder, although a recent study investigating the use of a filter-based cerebral embolic protection device during TAVR found less IHPOD in individuals in the filter group (3%) than in those without a filter (15%). 39 Moreover, the prospective, randomized evaluation of the TriGuard HDH Embolic Deflection Device During TAVI (DEFLECT III) trial showed 40% to 50% reduction of new cerebral DWI lesions after TAVR and better neurocognitive performance at discharge and 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…4,23,24) Postoperative delirium, a common complication after cardiac surgery, is also associated with increased mortality rates and cognitive decline. [25][26][27] New ischemic lesions created by cerebral microemboli have been considered to be significant risk factors for delirium, 28) and inflammation due to emboli has been considered to alter the permeability of the bloodbrain barrier, activate microglia, and influence cognitive impairment. 29,30) Carotid artery stenosis of more than 50%, advanced arteriosclerosis, and myocardial infarction also play important roles in delirium after OPCAB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with preoperative brain MRIs found cerebral atrophy, white matter hyperintensities, and cortical infarcts were risk factors for postoperative delirium. 9,12 These structural changes affect neural network function and may thus predispose to delirium.…”
Section: Pathophysiologymentioning
confidence: 99%